Kualitas pelayanan perpustakaan pad perpustakaan pascasarjana Universitas Sriwijaya Palembang Tahun 2008 - AKBAR, Meidi Abdul ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Library user satisfaction is determined by served quality has been given from library to the people who used that library, because of that quality of library services must to be the first priority in implementation of library. Therefore this research means for description library service quality and for to knowing what factors which is influence served quality of that library. The research method used in this research is descriptive method with qualitative approaches. Informants in this research were taken from university students whom used the library and librarians. The data obtained through observation, interviews and study documentation. Location this research doing at the library of Graduate Program of Sriwijaya University Palembang. The result of this research showed that the quality of library services at the library of Graduate Program of Sriwijaya University Palembang hasn’t optimal, this case seen from there is complaints from library users about collection still minus and hasn’t proper with user need, internet facilities are not satisfactory user, because the internet connection is slowly, unfavorable daycare items facilities, and there are not facilities photocopy and prayer room (musholla) which is well. The results of this research also showed that hasn’t optimal quality of library services at the library of Graduate Program of Sriwijaya University Palembang is influenced by the lack of professional human resources in managing the library, but that obstacle at least afford by the leadership role of the library who always giving guidelines, motivation, and has established good communication with subordinates.